EFFECT OF WORK ENVIRONMENT AND WORK MOTIVATION AND COMPETENCY ON EMPLOYEE PERFORMANCE - Fitriansyah Fitriansyah; Achmad Rizani; Aditya Shiro Ramadhan; Muhammad Junaedi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study aims to analyze and explain the effect of work environment and work motivation and competence on employee performance; The population in this study were employees of PT Gema Soerya Samodra, totaling 40 people. The sample selection technique used the Total Sampling Approach with a sample size of 40 people. Data collection techniques using questionnaires. The analysis was carried out using Partial Least Square (PLS) with the SmartPLS application version 3.8.9 and using SPSS Version 25 to test the validity and reliability of the respondents. The results showed that: Keywords : Work Environment, Work Motivation, Competence and Employee Performance